Gaya Kepemimpinan Partisipatif Lurah Kelurahan Sario Kotabaru Kecamatan Sario Kota Manado - Kogoya, Orina; Mokalu, Benedicta J.; Kalangi, Johny A.F. (AGRI-SOSIOEKONOMI, 2023)
The purpose of the study was to explain and analyze the participatory leadership style of the lurah and the performance of the Sario Kotabaru Urban Village apparatus of Manado City. The research was conducted in April 2022, the research site was at the Sario Kotabaru Manado Urban Village office. This research focuses on the participatory leadership style of the head of Sario Kotabaru Manado Urban Village and focuses on the performance of the head of village and the Sario Kotabaru Manado Urban Village apparatus. Informants consisted of lurah, 4 (four) kelurahan employees, 5 (five) residents of Sario Kotabaru Manado Village. Data collection uses observation, interviews and literature studies. Furthermore, data sources consist of primary data and secondary data and data analysis techniques consist of data reduction, data presentation, and data verification. The data verification process is a stage of testing the validity of the data and the meanings of the data so it is called the stage that determines the truth, strength, and suitability of the data. The results showed that the performance of the lurah and apparatus of Kelurahan Sario Kotabaru Kota Manado generally received positive appreciation from the community because they succeeded in building good performance with the community, remained alert to provide services, and were smart in empowering all potential to ward off COVID-19.